Shift in Learning Motivation in Improving Student Achievement at SMA Sutomo 1 Medan: A Sociological Perspective Analysis - Sihombing, Grace Prima Apriani (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to analyze the shift in learning motivation among high-achieving and non-academic students at SMA Sutomo 1 Medan. From a sociological perspective, learning motivation is influenced by socio-cultural factors that shape students' perceptions of success. This qualitative study uses a descriptive approach, utilizing primary data obtained from in-depth interviews, observations and documentation of 18 high-achieving students from grades X, XI, and XII. In addition, this study also uses a questionnaire by distributing an online google form questionnaire as a secondary data collection process to validate the truth of the qualitative research results. The research findings indicate a shift in students' learning motivation, where learning is no longer driven primarily by the development of self-knowledge but more by the desire to make parents proud. This study highlights how cultural education patterns from various ethnic backgrounds shape students' motivation, shifting them from intrinsic to extrinsic goals. These findings provide insights for teachers, schools, and parents to foster positive learning motivation. Further research is encouraged to explore the influence of multicultural education on learning motivation.